2020
DOI: 10.3390/en13051195
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Robust Adaptive Controller for the Pitch and Torque Control of Wind Turbines

Abstract: In this paper, robust adaptive control is designed for pitch and torque control of the wind turbines operating under turbulent wind conditions. The dynamics of the wind turbine are formulated by considering the five degrees of freedom system (rotor angle, gearbox angle, generator angle, flap-wise deflection of the rotor blade, and axial displacement of the nacelle). The controller is designed to maintain the rotor speed, maximize the aerodynamic efficiency of the wind turbine, and reduce the loads due to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Equations ( 8) and (9) shown that the stator current is controllable with the rotor current. With the omission of the stator resistance because it is so small, the stator flux can be assumed to be constant and its value is,…”
Section: Dfig Control Equations and Reference Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations ( 8) and (9) shown that the stator current is controllable with the rotor current. With the omission of the stator resistance because it is so small, the stator flux can be assumed to be constant and its value is,…”
Section: Dfig Control Equations and Reference Systemmentioning
confidence: 99%
“…DFIG generators provide access to the rotor windings and regulating the rotor voltage, the generator active and reactive powers are fully controllable. Therefore, the design and implementation of a new control scheme for a DFIG based wind turbine system has attracted the attention of several authors in the last years [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Learning and forgetting with learning rate (LF-LR). The previous methods do not forget any previous reward; this may be effective for steady systems but for changing models it might be advantageous to forget some previous rewards, Equation (13). The forgetting factor is modelled as the complementary leaning rate (1 − α).…”
Section: Policy Update Algorithmmentioning
confidence: 99%
“…In Yin et al [12], an adaptive robust integral SMC pitch angle controller and a projection-type adaptation law are synthesized to accurately track the desired pitch angle trajectory, while it compensates model uncertainties and disturbances. Bashetty et al propose an adaptive controller for pitch and torque control of the wind turbines operating under turbulent wind conditions [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation